2014
DOI: 10.1016/j.jsb.2014.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of Ophiostoma piceae sterol esterase: Structural insights into activation mechanism and product release

Abstract: Sterol esterases are able to efficiently hydrolyze both sterol esters and triglycerides and to carry out synthesis reactions in the presence of organic solvents. Their high versatility makes them excellent candidates for biotechnological purposes. Sterol esterase from fungus Ophiostoma piceae (OPE) belongs to the family abH03.01 of the Candida rugosa lipase-like proteins. Crystal structures of OPE were solved in this study for the closed and open conformations. Enzyme activation involves a large displacement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…Comparison of the structures of different lipases from the C. rugosa- like family indicates the importance of both the shape and amino acid composition of the internal tunnel, and their relationship with the kinetic properties of these proteins [3, 7, 8]. The analysis of putative intramolecular tunnels in the ancestral lipases showed that its size increased along evolution (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of the structures of different lipases from the C. rugosa- like family indicates the importance of both the shape and amino acid composition of the internal tunnel, and their relationship with the kinetic properties of these proteins [3, 7, 8]. The analysis of putative intramolecular tunnels in the ancestral lipases showed that its size increased along evolution (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…They are able not only to catalyze hydrolysis reactions under aqueous conditions, but also to carry out synthesis reactions, such as esterification and transesterification, in the presence of organic solvents [2]. All of them display the α/β-hydrolase fold, with their catalytic machinery formed by a catalytic triad (serine, histidine and glutamic acid) and the oxyanion hole [3]. These enzymes are present from microbes to plants and animals, and are widely applicable in industrial processes, such as biofuels, oleochemical, food, detergents, cosmetics, pharmaceutical, textile and paper industry, due to their versatility and stability to harsh conditions [4].…”
Section: Introductionmentioning
confidence: 99%
“…The pPIC9:PlicBconstruct was transformed into P . pastoris KM71 and GS115 strainsas described before [ 13 ].Activity screening was performed using single colonies from the transformation plates grown in 20 mL YEPS medium in 100 mL flasks with 0.5% w/v of methanol to induce gene expression. The flasks were incubated at 28°C and 250rpm and 0.5% w/v methanol was added daily for maintaining the induction.…”
Section: Methodsmentioning
confidence: 99%
“…(Ghosh et al 1991), plants (Pringle and Dickstein 2004), and animals (Finer et al 2004), and may be applied in valuable biological processes. The efficient hydrolysis of both triglycerides and sterol esters using sterol esterase from Ophiostoma piceae has been successfully applied for pitch control in the pulp and paper industry (Coloma et al 2015;Gutiérrez-Fernández et al 2014;Calero-Rueda et al 2002). Steryl and cholesteryl esterases from Pseudomonas sp.…”
Section: Microorganisms Producing Esterasesmentioning
confidence: 99%